2018
DOI: 10.3390/s18124423
|View full text |Cite
|
Sign up to set email alerts
|

Intention Estimation Using Set of Reference Trajectories as Behaviour Model

Abstract: Autonomous robotic systems operating in the vicinity of other agents, such as humans, manually driven vehicles and other robots, can model the behaviour and estimate intentions of the other agents to enhance efficiency of their operation, while preserving safety. We propose a data-driven approach to model the behaviour of other agents, which is based on a set of trajectories navigated by other agents. Then, to evaluate the proposed behaviour modelling approach, we propose and compare two methods for agent inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The model therefore is less generalisable compared to the geometric model presented above, as the trajectories recorded inside a single specific roundabout would represent vehicles’ behaviour only in that roundabout. This modelling approach was also used in our previous study [39]. A set of reference trajectories constituting such a roundabout model is presented in Figure 1b.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The model therefore is less generalisable compared to the geometric model presented above, as the trajectories recorded inside a single specific roundabout would represent vehicles’ behaviour only in that roundabout. This modelling approach was also used in our previous study [39]. A set of reference trajectories constituting such a roundabout model is presented in Figure 1b.…”
Section: Methodsmentioning
confidence: 99%
“…Having one of the above three models at hand, as a new query trajectory begins to comes in, the first task is to predict what exit direction is the agent expected to take (to leave the roundabout) so that more precise predictions such as future agent state can be estimated. For the purpose of exit direction classification, we use and build upon our previous work [39], where we proposed exit direction classification using a decision-tree based as well as a particle-filtering based approach, using heading angle, lateral position offset and speed as feature attributes. The study showed that, in a multi-class problem such as the roundabout, the particle-filtering based approach performed better.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presented approaches [6], [7], [8] focused warehouse scenario, behavior modeling using trajectories, and collision avoidance considering the human intention to avoid a collision, to model the human behavior for navigation and successful navigation in warehouse scenario. Once again the prior definition of human intention was not defined.…”
Section: B Intention Based Road / Pedestrian Synchronized Safe Vehiclementioning
confidence: 99%